MEDAN SEMANTIK METAFORA NOMINATIF DALAM LIRIK LAGU KLa PROJECT DAN BON JOVI SERTA KAITANNYA DENGAN SISTEM EKOLOGI - , M. Imelda Kusumastuty, Prof. Dr. Soepomo Poedjosoedarmo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research focuses on the analysis of nominative metaphors found in the song lyrics of an Indonesian music group, KLa Project, and an American music group, Bon Jovi. The objectives of the research are to identify and describe the semantic field of the nominative metaphors, then to analyze them comparatively and contrastively to observe the relationship to the ecological system and culture. The method of data gathering used in the research is library research. The primary data source is the lyrics of 20 (twenty) KLa Project and Bon Joviâs songs. The method of data analysis used is equivalency method, in which the semantic field of the nominative metaphors are identified and discussed in relation to the ecological system. The method of data presentation used is formal presentation method. The result of the research are as follows: (1) The distribution of the semantic field category shows that there is an imbalance in the ecological system around the creators of the metaphors, (2) The existence of metaphors can be used to indicate the quality of the lyric writing process, (3) 83, 89% of the metaphors are abstract concepts symbolized by concrete concepts, and (4) Metaphors can be used to observe the social and cultural condition around the creators of the metaphors.